Credit Stimulus, Executive Ownership, and Firm Leverage - Chakraborti, Rajdeep; Dahiya, Sandeep; Ge, Lei; Gete, Pedro (Management Science, 2022)
We show that executive ownership is a significant driver of the demand for credit following credit expansion policies. Our focus on credit demand is in contrast to most studies that have focused on credit supply factors such as bank capital. Our identification exploits the large and unexpected Chinese credit expansion in 2008. This setting offers a unique advantage as in 2008 the Chinese government had almost complete control over the banking sector and it directed the banks to increase credit supply. Thus, in this setting, demand, rather than supply, largely drives the observed changes in firms’ borrowing. We provide extensive robustness tests to validate our results. This paper was accepted by Kay Giesecke, finance.